(3LfSjI GdTQcI (B:s (3OQGSI ebGQfI (B/s - (3NGdO, gTGes ((3GdEScfOQjI(B: s (3OGQ GdacQ GdLGeYj(B, s, 2012)
(3LfSjI GdTQcI eYGjjQ KHhJgG(B- (3LfSjI GdTQcI Hjf GdEfcGQ hGdbHhd(B- (3eYGjjQ KHhJ LfSjI GdTQcI (B- (3LfSjI GdTQcI aj GdbGfhf GdeUQj (B- (3eYGjjQ KHhJ GdLfSjI GdeUQjI ddTQcIs
Keywords: (3GdTQcGJs; (3GdTQcGJ GdOhdjIs